The Need to Strengthen the Role of the Pharmacist in Sri Lanka: Perspectives - M.H.F. Sakeena; Alexandra A. Bennett; Andrew J. McLachlan (MDPI AG, 2019)
The role of the pharmacist in healthcare has evolved greatly over the last half-century, from dispensing to providing direct patient-oriented activities not associated with dispensing. However, pharmacist-led healthcare services in Sri Lanka must undergo reform to fully take advantage of their expertise and training in medicine management and related outcomes in Sri Lankan patients. As befits a profession’s role development and value, professional and educational standards for pharmacists need ongoing development and growth. Currently, university curricula and continuing professional education in Sri Lanka require further development and optimisation to provide the theoretical and practical knowledge and skills regarding quality use of medicines and patient-oriented care. Furthermore, pharmacists’ roles in Sri Lankan hospital and community pharmacist settings need to be recognised and should include the pharmacist as an integral part of the multidisciplinary healthcare team in Sri Lanka. Studies from developed countries and some developing countries have demonstrated that expanded pharmacists’ roles have had a significant positive cost-effective impact on the population’s health. Therefore, the availability of qualified Sri Lankan pharmacists trained to deliver expanded professional services accompanied by greater pharmacist integration into healthcare delivery is crucially important to ensure quality use of medicines within the Sri Lankan healthcare system and optimise the medication-related needs of Sri Lankans.